193k views
1 vote
How do you do this function (3k - 5)(k + 2)

User David Ross
by
5.2k points

2 Answers

5 votes

Answer:

3k² + k - 10

Explanation:

Given

(3k - 5)(k + 2)

Each term in the second factor is multiplied by each term in the first factor, that is

3k(k + 2) - 5(k + 2) ← expand both parenthesis

= 3k² + 6k - 5k - 10 ← collect like terms

= 3k² + k - 10 ← in expanded form

User Sudharsan Selvaraj
by
4.5k points
1 vote

Answer:

3k² + k - 10

Explanation:


\text{Use FOIL:}\ (a+b)(c+d)=ac+ad+bc+bd\\\\(3k-5)(k+2)\\\\=(3k)(k)+(3k)(2)+(-5)(k)+(-5)(2)\\\\=3k^2+6k-5k-10\qquad\text{combine like terms}\\\\=3k^2+(6k-5k)-10\\\\=3k^2+k-10

User Nick Husher
by
5.0k points